Two types of modern sediment dispersal systems in the western Taiwan foreland basin: Sediment transfer from basin to basin - Cheng‐Shing Chiang; Kan‐Hsi Hsiung; Ho‐Shing Yu (The Depositional Record)
Abstract The western Taiwan foreland basin (WTFB) is a classical peripheral foreland basin longitudinally bounded by the East China Sea (ECS) to the north and the South China Sea (SCS) to the south. Sediments spill longitudinally into the nearby marginal ocean basins, similar to the typical foreland basin setting. Due to oblique collision in the Taiwan region, the WTFB has evolved into two subbasins: a mature basin dominated by fluvial sediments in central‐northern Taiwan and an immature one dominated by deep marine facies offshore south‐western Taiwan, accompanied by two distinct sediment routing systems. In the north, the Choushui River drainage, narrow seaway of the Taiwan Strait, Huapingshu Channel/Mienhua Canyon System and southern Okinawa Trough (SOT) are integrated into a united sediment dispersal system, allowing sediments sourced by the mature basin to laterally overflow into the ECS and be deposited into the SOT. In southern Taiwan, the Kaoping River drainage, Kaoping submarine canyon, Penghu submarine canyon, deep‐sea Penghu Channel and SCS basin interconnect, forming a longitudinal dispersal system for sediments mainly derived from the southern Taiwan orogen to be longitudinally transported to the northern SCS basin and the northernmost Manila Trench. The oblique collision between the Luzon Arc and the Chinese margin in the Taiwan region is the major factor in the development of two distinct sediment dispersal systems. Preferential sediment transport (axial vs. transverse), shelf width and sea‐level change since the Last Glacial Maximum (~2 ka BP) are the other significant factors in the development of sediment routing systems in the WTFB. The two proposed distinct sediment dispersal systems in the WTFB clearly demonstrate how foreland basin sediments can be transferred longitudinally to adjacent marginal sea basins. Moreover, the sediment dispersal systems in the WTFB can be considered a modern analogue for interpreting ancient counterparts.